مشكلات التنشئة الاجتماعية في الأسر المطلقة دراسة مقارنة داخل المجموعة أبناء الأسر المطلقة لتلاميذ الثانوية بمدينة الأغواط - بن الشيخ مروة; فرطاس كريمة; مريجة عباس (My University, 2021)
This research aims to identify the problems of socialization for children of divorced families, to achieve these goals, we used the descriptive approach, and information was collected from (30) male and female students in an intentional way. Using the statistical package for social sciences (spss) by applying the (t) test, the research concluded a set of results, the most important of which are: The dominant characteristic is parental sympathy, meaning that children seek the sympathy and tenderness of their parents (father, mother.( -There are statistically significant differences in the parental or familial treatment of adolescents from families of divorce according to the sex difference between the two samples of males and females. -There are statistically significant differences in the parental or familial treatment of adolescents from families of divorce due to the level variable.social problems; families; divorce